Morusin as a drug candidate: opportunities, limitations, and the path toward clinical translation - Azzam, Hany N.; El-Dessouki, Ahmed M.; Attallah, Kareem A.; Sadek, Mohamed A.; Aboulmagd, Yara M.; Hassan, Mennat-Allah M.; Fahmy, Mohamed I.; El-Shiekh, Riham A.; Kamal, Rania M.; Khalifa, Hazim O. (Frontiers in Pharmacology, 2025)
Prenylflavonoids are widespread in plants, which are considered valuable sources of natural polyphenolic compounds with isoprenyl groups, including flavones, flavanones, chalcones and aurones. Among the notable prenylated flavonoids, morusin-a prenylated flavone isolated from the bark of white mulberry, has garnered attention for its multifaceted biological activities. Extensive research has demonstrated that morusin exhibits pronounced analgesic, antioxidant, anti-inflammatory, bone repair, antitumor, cardioprotective, neuroprotective, hepatoprotective, antidiabetic, and antimicrobial effects. The enhanced lipophilicity imparted by prenylation is believed to facilitate greater cellular membrane interaction, contributing to the superior bioactivity of these compounds compared to their non-prenylated derivatives. Unlike previous reviews that mainly emphasize morusin’s bioactivities, this article critically addresses its pharmacokinetic limitations, translational challenges, and safety concerns, offering a more integrated perspective on its path toward clinical application. This review aims to get current insights into the health-promoting effects of morusin, thereby informing the development of novel plant-derived pharmaceuticals and nutraceuticals within the prenylflavonoid category.